Second Language Learner Perceptions on Web-Based Language Learning - WMUSK Walisundara (Journal of English Language Teaching and Linguistics, 2020)
The focus of the current study was to investigate the perceptions of English as a second language learners on using computer assisted language learning (CALL) for improving academic writing skills. The study was conducted for thirteen weeks with 82 second year undergraduates from General Sir John Kotelawala Defence University in Sri Lanka. Switching Replication was used for the research design. The data were analyzed using mix method approach. The findings indicate that the participants preferred the in-class environment more than the CALL environment for academic writing skills.  Participants’ lack of experience in CALL, poor writing and vocabulary skills and the negative interference from the technical issues were some of the issues that had a negative effect on the participants in the CALL environment. Yet the success of the intervention both in the first and second phases indicates the effectiveness of CALL for developing academic writing skills